2021
DOI: 10.1111/ajt.16614
|View full text |Cite
|
Sign up to set email alerts
|

Between-center variation in high-priority listing status under the new heart allocation policy

Abstract: Under the new US heart allocation policy, transplant centers listed significantly more candidates at high priority statuses (Status 1 and 2) with mechanical circulatory support devices than expected. We determined whether the practice change was widespread or concentrated among certain transplant centers. Using data from the Scientific Registry of Transplant Recipients, we used mixed-effect logistic regression to compare the observed listings of adult, heart-alone transplant candidates postpolicy (December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Recent investigation by Ran et al supports the presence of such a phenomenon, noting increased center-level variation in high-priority listing status in the new era. 16 Such findings are in line with the variation in centerlevel tMCS use noted in our study and may give credence to the idea that a broad spectrum of patients may be listed as highpriority status following the policy change. To better assess equity in the effect of the policy change, standardization of criteria for the initiation of tMCS could play a critical role.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent investigation by Ran et al supports the presence of such a phenomenon, noting increased center-level variation in high-priority listing status in the new era. 16 Such findings are in line with the variation in centerlevel tMCS use noted in our study and may give credence to the idea that a broad spectrum of patients may be listed as highpriority status following the policy change. To better assess equity in the effect of the policy change, standardization of criteria for the initiation of tMCS could play a critical role.…”
Section: Discussionsupporting
confidence: 87%
“…3 Interestingly, some have suggested that these findings may be a manifestation of "gaming" the new system and patient advocacy, with physicians choosing bridging modalities that optimize the odds of transplantation for their patients. 11,16 In light of these changes, we found patients listed at high-tMCS centers to exhibit higher transplantation rates and lower rates of PWO compared to those listed at low-tMCS centers. These findings build on prior literature, showing that center-level tMCS use may profoundly impact patient-level outcomes regardless of the patient bridging strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To control for changes in recipient demographics over time, we estimated the effect of the policy using a multivariable Cox proportional hazards regression controlling for the components of the Index for Mortality Prediction After Cardiac Transplantation (IMPACT) score using the entire study data range 15 . Because treatment practices have changed since the new policy was implemented, 16,17 we also estimated posttransplant survival before and after policy implementation by treatment support at the time of transplantation. For these subgroup analyses, high‐dose inotrope support was defined by OPTN policies as “multiple inotropes or a single high‐dose inotrope and has hemodynamic monitoring” (e.g., dobutamine at greater than or equal to 7.5 mcg/kg/min) 11 .…”
Section: Methodsmentioning
confidence: 99%
“…However, a widespread behavior shift to achieve expeditious transplantation has unfortunately been observed with a higher than expected number of patients across centers nationwide being listed with high-priority statuses (Status 1 or 2) without accompanying explanatory changes in candidate characteristics when compared to seasonally matched prepolicy cohorts. 7 Furthermore, the number of exception requests for high-priority listing has dramatically increased. Combining these factors, the new heart allocation policy has had limited success in reducing the crowding of candidates clustered at the highest priority statuses, a behavior which has been observed broadly across transplant centers in the United States.…”
mentioning
confidence: 99%
“…However, a widespread behavior shift to achieve expeditious transplantation has unfortunately been observed with a higher than expected number of patients across centers nationwide being listed with high‐priority statuses (Status 1 or 2) without accompanying explanatory changes in candidate characteristics when compared to seasonally matched prepolicy cohorts 7 . Furthermore, the number of exception requests for high‐priority listing has dramatically increased.…”
mentioning
confidence: 99%